David Lynch [videorecording (DVD)] : the art life - Lynch, David, 1946- (Criterion collection, 2017)
An absorbing portrait of the filmmaker David Lynch, as well as an intimate encounter with the man himself. From the privacy of his home and painting studio in the Hollywood Hills, a candid Lynch conjures people and places from his past, from his boyhood in Idaho and Virginia to his experiences at art school in Boston and Philadelphia to the beginnings of his filmmaking career in Los Angeles, in stories that unfold like scenes from his movies.